Monge–Kantorovich equation for degenerate Finsler metrics. (May 2021) - Nguyen, Van Thanh
Abstract: The paper establishes that a generalization of Monge–Kantorovich equation gives rise to a necessary and sufficient optimality condition for the Kantorovich dual problem and minimal flow problem associated with a very degenerate Finsler metric without any assumption on coerciveness.